Reward-based biobehavioral marker in anhedonic and hypomanic/manic symptomatology - Chaney, Grace-Anna (My University, 2017)
Aberrant reward sensitivity has been an established hallmark of bipolar disorder (BD) and major depressive disorder (MDD), and there is now evidence for a potential biomarker for this abnormality, termed frontal alpha asymmetry. Those with BD exhibit greater relative left hemispheric activity, and those with MDD show greater relative right frontal activity, during challenging, reward-based tasks. The present study utilized a sample of 30 Towson University students and measured their levels of anhedonic and manic symptomatology, the two characteristic symptoms of MDD and BD, respectively. While recording their brain activity via electroencephalogram equipment (EEG), they completed a word unscrambling task that increased in difficulty and was either paired with a potential reward or punishment. Although not significant, positive and negative relationships between the frontal asymmetry index during the hard/reward trials and manic and anhedonic symptomatology, respectively, were revealed, as expected. The present trends are consistent with previous findings for a neural marker of approach motivation in these pathologies, and warrants more extensive inquiry in larger, clinical samples.
(M.A.) -- Towson University, 2017